An Inherited Genetic Variant in CEP72 Promoter Predisposes to Vincristine‐Induced Peripheral Neuropathy in Adults With Acute Lymphoblastic Leukemia. Issue 3 (16th November 2016) - Stock, W; Diouf, B; Crews, KR; Pei, D; Cheng, C; Laumann, K; Mandrekar, SJ; Luger, S; Advani, A; Stone, RM; Larson, RA; Evans, WE
Abstract : Peripheral neuropathy is a major toxicity of vincristine, yet no strategies exist for identifying adult patients at high‐risk. We used a case–control design of 48 adults receiving protocol therapy for acute lymphoblastic leukemia (ALL) who developed vincristine‐induced neuropathy (NCI grade 2–4) during treatment, and 48 matched controls who did not develop grade 2–4 neuropathy. Peripheral neuropathy was prospectively graded by National Cancer Institute (NCI) criteria. CEP72 promoter genotype (rs924607) was determined using polymerase chain reaction (PCR)‐based single nucleotide polymorphism (SNP) genotyping. Frequency of the CEP72 T/T genotype was higher in cases (31% vs. 10%, P = 0.0221) and the incidence of vincristine‐induced neuropathy (grades 2–4) was significantly higher in patients homozygous for the CEP72 T/T genotype. 75% of the 20 patients homozygous for the CEP72 T allele developed grade 2–4 neuropathy, compared to 44% of patients with CEP72 CC or CT genotype ( P = 0.0221). The CEP72 polymorphism can identify adults at increased risk of vincristine‐induced peripheral neuropathy.